THE DISTRIBUTION OF COMMODITIES AMONG ISLANDS IN INDONESIA THROUGH THE HARBOUR - Herman Budi Sasono (e-Jurnal Kewirausahaan, 2014)
According to recent data, Indonesia consists of ±60.000 islands spread in whole Nusantara area under the equator line; of course it needs sea transportation handling which is neat and reliable. By using ships with huge Dead Weight, hopefully it make the distribution of commodity flow in the whole country can be equal, quick, and cheap, with purpose that the price of commodity and service in one island which has more production and in other island which is lack not much different. Sea channels, especially when about to enter to the local and pioneer parts which have many inhabitants must at Dredging (rich the deep of 15-20 meter, wide of 30-50 meter in minimal); port’s medium like: dock, building’s warehouse or field’s warehouse, land crane, gantry crane, vorklift, navigation, postpone ship, guide ship and SDM (human resource) are prepared and built, and also land streets and bridges to / from industrial centrals / hinterland to the sea port have to be built. Trade – interinsular certainly have economic aspect, because in their realization appears various cost and revenue that have to be received by the agent (consignee) namely: commodity’s owner, cruise office, Perusahaan Bongkar Muat (PBM) / Unload Loading Company, line warehouse manager – I, truck transportation entrepreneur / Pengusaha Angkutan Truk (Organda), fumigation service entrepreneur, superindent service entrepreneur, and so on. Many problems that appears when interinsular realization are: nature disturbance like heavy rain that not stop and cause the ship’s unload loading process blocked, hurricane and sea wave which can shake the content when fly and pulled by shape crane / gantry crane; this situation caused unload loading have to be delayed, and also the deep of set and subside of sea water surface (tide tables) that not maximal, it make bulk carriers (kapal curam) with the contain of 100.000 metric ton that will enter to Tanjung Priok Port, Tanjung Emas, Tanjung Perak, and others must do sea lightering (unload in the midst of sea) first until they remains 50.000 Metric Ton, so the ship can move to the port’s dock to continue unload the rest of the contain; and if also line warehouse - I have been full by export commodities – whereas the flow of export commodity interisland still continually come to be loaded to ship, then have to be done Truck Lossing / Truck Loading, and it is certainly concern with cost. Keyword: distribution, commodity, harbour industry